Pengaruh Brand Image dan Brand Trust Terhadap Minat Beli The Originote (Studi pada Universitas Negeri di Kota Malang) - Denada Nabila; Rizky Kurniawan Murtiyanto; Arni Utamaningsih (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
The development of skincare products in Indonesia has seen rapid progress in recent years, in line with the increasing public awareness of the importance of skin care. The Originote, as one of the brands that uses niacinamide, provides an alternative for consumers looking for effective and affordable skin care solutions. However, the niacinamide content of The Originote serum does not match its claims. This study aimed to investigate the influence of brand image and brand trust on purchase intentThe data collection was conducted with an online questionnaire administered to 100 female university students from state universities in Malang City. The sampling was performed with non-probability sampling and purposive sampling techniques. The data analysis in this study used multiple linear regression analysis and hypothesis testing.  The results of the classical assumption test indicated that the data met the criteria. The results of the coefficient of determination test were 0,801 meaning that 80.8% of the variation was influenced by other variables. The results of the hypothesis test indicate that brand image and brand trust partially and simultaneously have a significant effect on the purchasing interest of female students in Malang City.